Impact of Child Abuse on Academic Performance of Pupils in Public Primary Schools i n Kieni West Sub - County, Nyeri County. - Ngisa, Francisca Sarange; Muriungi, Pamela; Mwenda, Eric (International Journal of Business and Management Invention, 2017)
Child abuse has become a global problem that needs to be tackled if children are to be given the right to education and freedom. Early exposure to adverse childhood experiences including physical, sexual, and emotional abuse; neglect; violence; household dysfunction; parental substance abuse or mental illness; and an absent parent are strong predictors of poor academic performance. The main objective of this study was to investigate the impact of child abuse on the academic performance of pupils in public primary schools in Kieni West Sub-county, Nyeri County. The study adopted a descriptive survey research design. The target population for this study comprised 52 head teachers, 560 teachers and 2,275 pupils. A sample of 26 head teachers, 280 teachers and 228 pupils was selected using proportionate random sampling. Data was collected through questionnaires and interview schedules. Descriptive statistics were used to analyse the quantitative data and content analysis was used to analyse the qualitative data. Relationship between variables was tested using the Chi-square test. The findings of the study showed that pupils had low level of awareness of child abuse. Child abuse was found to affect school attendance, pupils’ behaviour and learning disorders negatively and all the hypotheses were therefore rejected
Keywords: Academic Performance; Child abuse; Learning disorder; Pupils’ behaviour; School attendance